Evolution of neonatal mortality by preventable causes over the past ten years in Espírito Santo State - Glícia Chierici Baptista; Wanêssa Lacerda Poton (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: analyze neonatal mortality causes, highlighting the pteventable ones from 2008 to 2017, in Espírito Santo State and health regions. Methods: ecological study of temporal series on neonatal mortality using data from Mortality Information System and from Live Birth Information System. The death causes were classified based on the List of Avoidable Causes of Deaths due to Interventions of the Brazilian Health System. The temporal tendency was analyzed using linear regression. Results: the neonatal mortality rate reduced, approximately 5%, with a reduction of almost 27% in the late neonatal component. Approximately, 70% of neonatal deaths were preventable, with a higher frequency of reducible causes by adequate care at pregnancy, childbirth and to the newborn. The reduction was significant for adequate care for pregnant women in Espírito Santo and in Metropolitan Region and due to adequate care to the newborn in the South Region. Conclusions: the main causes of neonatal deaths were due inadequate care for women during pregnancy, at childbirth and to the newborn, despite the reduction in neonatal mortality over the past 10 years. This study may contribute to the planning of health policies to improve care for pregnant women, parturient and to the newborn.